Comparison between online and traditional teaching-learning among non-clinical medical students (BIRDEM Medical Journal, 2021)
Background: Medical institutes remained on complete shut down during the coronavirus disease of 2019 (COVID-19) pandemic while Information Technology (IT) bridged the teaching learning between the students and teachers. The study objectives were to determine the opportunities and obstacles of teaching learning process and overall effectiveness of online classes over traditional classes.Methods: A cross-sectional study was conducted from July 2020 to December 2020 between students and teachers of Khulna city Medical College, Khulna, Bangladesh. An online questionnaire was developed using google form containing four sections about different aspects of IT and teaching learning process.Results: Around 87% (160 vs 48) students and teachers responded to the questionnaire. The most preferred online teaching learning platform for students and teachers was zoom (84.4% vs 83.4%) and the favored devices were smart phone (96.2% vs 87.5%) followed by laptop computer (90.6% vs 83.3%). The majority felt connected to each other (82.5% vs 62.5%) and could work faster and effectively (75% vs 66.7%). Conversely, students (65.6%) felt online learning was more enjoyable than teachers (29.2%), where significant difference was found; (p= 0.006). Poor network (98.1% vs 79.1%) and affordability of mobile data (81.2% vs 66.7%) were the two main barriers among them. On-line teaching-learning neither increased student- teacher interaction (51.9% vs 66.7%), nor had better scope of asking question (52.5% vs 70.8%) and there was less scope of explaining details (52.5% vs 66.7%). Oral assessment was the most preferable (89.4% vs 83.3%), but the practical assessment (78.1% vs 83.3%) was the least preferable method for assessing students’ knowledge and skill online. Overall effectiveness of online classes over traditional classes was scored around 50% (±10%) by students and teachers (58.1% vs 62.5%).Conclusion: Despite having barriers like poor network, data affordability and limited computer and net usability, online classes played a pivotal role to continue the academic activities in a medical college during Corona pandemic.BIRDEM Med J 2022; 12(1): 45-50